Development and characterization of elephant foot yam starch based pH‐sensitive intelligent biodegradable packaging. (9th February 2022) - Singh, Rashmi; Kaur, Jasjot; Bansal, Radhika; Sharanagat, Vijay Singh; Singh, Lochan; Kumar, Yogesh; Patel, Ajay
Abstract: In the present study, biodegradable intelligent films (pH indicators) were developed using elephant foot yam starch and Xanthan gum in the combination of red cabbage (RC, anthocyanins) and Beetroot (BR, betalain) (10% to 40%). Fourier‐transform infrared spectrum confirmed that the increase in extract concentration did not affect the chemical bonding, but it decreased the film's moisture content, water activity, and solubility. The addition of extract increased the phenolic, flavonoid, and antioxidant activity of the film. The film showed an excellent response (color change) for different pH levels, and the color transition from purple to deep pink in the acidic medium and purple to green in the basic medium was observed for RC films. However, the color transition for BR films was from red to brown in the acidic medium and from red to yellow in the acidic medium, hence it can be used as spoilage indicates for different food products. Abstract : Practical Application: The developed packaging film can be used to indicate the pH‐based changes in different food products. It has good antioxidant activity that inhabits the microbial degradation making it suitable for packaging of perishable foods.